2006
DOI: 10.1158/1078-0432.ccr-05-1698
|View full text |Cite
|
Sign up to set email alerts
|

Stress Hormone–Mediated Invasion of Ovarian Cancer Cells

Abstract: Purpose: There is growing evidence that stress and other behavioral factors may affect cancer progression and patient survival.The underlying mechanisms for this association are poorly understood.The purpose of this study is to determine the effects of stress-associated hormones norepinephrine, epinephrine, and cortisol on the invasive potential of ovarian cancer cells. Experimental Design:The ovarian cancer cells EG, SKOV3, and 222 were exposed to increasing levels of either norepinephrine, epinephrine, or co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

16
367
1
8

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 442 publications
(401 citation statements)
references
References 59 publications
16
367
1
8
Order By: Relevance
“…Therefore, the beneficial effects of propranolol and etodolac seem not to be mediated by directly affecting B16 or 3LL secretion of VEGF, nor by reducing stresshormone-induced increase in VEGF secretion by these tumor cells. Nevertheless, in vivo tumor responses may differ from the in vitro setting, and Sood et al have also shown that CAs can increase MMP2 and MMP9 secretion by tumor cells and accelerate tumor invasion capacity (20). Therefore, other direct effects of stress hormones on tumor cells, which were not tested herein, could clearly be involved and mediate the beneficial effects evident in this study.…”
Section: Sectionmentioning
confidence: 69%
See 2 more Smart Citations
“…Therefore, the beneficial effects of propranolol and etodolac seem not to be mediated by directly affecting B16 or 3LL secretion of VEGF, nor by reducing stresshormone-induced increase in VEGF secretion by these tumor cells. Nevertheless, in vivo tumor responses may differ from the in vitro setting, and Sood et al have also shown that CAs can increase MMP2 and MMP9 secretion by tumor cells and accelerate tumor invasion capacity (20). Therefore, other direct effects of stress hormones on tumor cells, which were not tested herein, could clearly be involved and mediate the beneficial effects evident in this study.…”
Section: Sectionmentioning
confidence: 69%
“…reported to affect angiogenic-related processes (2,19,20), which can synergistically affect tumor progression. To further estimate the efficacy of the combined drug regimen, we compared it to poly(I:C) and to IL-12 administration, two wellestablished experimental interventions reported to control tumor progression (31).…”
Section: Sectionmentioning
confidence: 99%
See 1 more Smart Citation
“…potentiate the proliferation and migration of the cancer cells, inhibit the tumor cell apoptosis, increase the tumor cell invasiveness and metastatic activity, support the neoangiogenesis in the tumor tissue, or suppress the natural killer cell activity (Godbout and Glaser 2006;Sood et al 2006;Th aker et al 2006;Andersen et al 2007;Sephton et al 2009;Hassan et al 2013;Nagaraja et al 2013). Th ese eff ects are mediated especially by neurotransmitters released by sympathetic nerve endings, particularly by norepinephrine (Yang 2010).…”
mentioning
confidence: 99%
“…For instance, surgical stress induces the release of catecholamines that act on adrenergic receptors located in the membrane of cancer cells, thus stimulating their proliferation and invasiveness [33,34]. Opioids are the most commonly used analgesics in the perioperative period.…”
Section: Introductionmentioning
confidence: 99%